2020
DOI: 10.1007/s00330-020-06942-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the clinical decision support tool ESR eGUIDE for teaching medical students the appropriate selection of imaging tests: randomized cross-over evaluation

Abstract: Objectives To evaluate ESR eGUIDE—the European Society of Radiology (ESR) e-Learning tool for appropriate use of diagnostic imaging modalities—for learning purposes in different clinical scenarios. Methods This anonymized evaluation was performed after approval of ESR Education on Demand leadership. Forty clinical scenarios were developed in which at least one imaging modality was clinically most appropriate, and the scenarios were divided into sets 1 and 2. These sets were provided to medical students rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…This finding is consistent with conclusions from a review by Kim et al, describing how most of the existing literature on e-learning interventions have little quantitative data, evaluate a limited range of outcomes and have significant gaps in study designs [72]. Additionally, only 13 (31%) randomized control trials (RCTs) were included in the review [26,[43][44][45][46][47][48][49][50][51][52][53][54]. Amongst these studies, five reported pre and post test scores [45,48,[52][53][54], three of which report long term follow up [45,52,54].…”
Section: Intervention Designsupporting
confidence: 85%
See 3 more Smart Citations
“…This finding is consistent with conclusions from a review by Kim et al, describing how most of the existing literature on e-learning interventions have little quantitative data, evaluate a limited range of outcomes and have significant gaps in study designs [72]. Additionally, only 13 (31%) randomized control trials (RCTs) were included in the review [26,[43][44][45][46][47][48][49][50][51][52][53][54]. Amongst these studies, five reported pre and post test scores [45,48,[52][53][54], three of which report long term follow up [45,52,54].…”
Section: Intervention Designsupporting
confidence: 85%
“…More than half of the studies were conducted in the European Union (21 studies). Several research designs were described, including 17 observational studies [25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], 13 randomised control trials [26,[43][44][45][46][47][48][49][50][51][52][53][54], three non-randomised control trials [55][56][57], eight qualitative studies [58][59][60][61][62][63][64][65], and one mixed methods study [66]. Thirteen of the total studies included data collection both pre-and post-intervention [25,27,31,34,36,38,…”
Section: Design Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…(https://www.changehealthcare.com/clinical-decision-support/careselect/imaging)) 10,13 . These tools have proven valuable in improving the diagnostic management of patients with various clinical conditions, resulting in lower rates of inappropriate examinations 3,14,15 .…”
Section: Introductionmentioning
confidence: 99%